Motivasi Kerja, Budaya Organisasi dan Kompetensi terhadap Kinerja Guru Pada SMK Muhammadiyah 3 Aek Kanopan - Taufik Hidayat; Hasrudy Tanjung; Azuar Juliandi (Universitas Pendidikan Nasional, 2020)
The purpose of this research is to know the work motivation, organizational culture and competence on the performance of teachers in SMK Muhammadiyah 3 Aek Kanopan. The population in this study is all teachers of SMK Muhammadiyah 3 Aek Kanopan that amounted to 40 people. The data collection techniques in this study are documentation and poll list. Data analysis techniques using multiple linear regression analyses, classical assumption Test T, Test f and coefficient of determination. Data processing in this study uses the program SPSS 22.00 for Windows Software. Based on the results of the research conducted, from the partial testing influence of work motivation to the performance of the teacher obtained the value of sig (2 tailed) amounting to 0.005 smaller than a 0.05, then the motivation is declared a significant effect on the performance of teachers . A partial testing of organizational culture influences the teacher's performance gained a sig value of 0.003 smaller than a 0.05, hence the organizational culture revealed to be a significant impact on teacher performance. A partial test of competency influence on the teacher's performance obtained a sig value of 0.022 smaller than a 0.05, so it is stated that the competency has significant effect on the teacher's performance. Simultaneous testing of the influence of work Motiovasi, organizational culture and competency in the teacher's performance obtained a sig value of 0.000 smaller than a 0.05, then expressed work motivation, organizational culture and competencies are significant effect on Teacher's performance.